Analisis Faktor-Faktor yang Berhubungan dengan Kejadian Computer Vision Syndrome Sebagai Dasar Upaya Pengembangan Kebijakan di PT X - Ananda, Nadiya; Liberty, Iche Andriyani; Utari, Sri; Nurdin, Nugi (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2025)
Computer Vision Syndrome (CVS) is a collection of symptoms arising from excessive computer use, including eye strain, watery eyes, itching, redness, dryness, blurred vision, and neck pain or headaches. According to WHO data, approximately 40–90% of workers who use computers experience CVS, as also reported by employees at PT. X. This study aims to analyze the relationship between factors such as age, length of service, gender, use of glasses, refractive disorders, eye rest time, working duration, lighting level, use of air conditioners, and Visual Display Terminal (VDT) settings with the incidence of CVS among PT. X employees. This mixed methods study involved 120 employees who work in front of computers daily. Data were collected using questionnaires, interviews, and observation, then analyzed both quantitatively and qualitatively. The results showed that 78.3% of respondents experienced CVS. Significant relationships were found between age, gender, years of service, use of glasses, refractive errors, eye rest time, lighting, and VDT arrangement with the occurrence of CVS. The main protective factor was the use of glasses, while dominant risk factors included suboptimal lighting and being male. These findings highlight the importance of promotive and preventive policies, such as eye health education, implementation of ergonomic SOPs, and regular health checks to reduce CVS prevalence and improve work productivity at PT. X.